The Development of Integrated Islamic Values E-book as Learning Media in Writing Class - Rini Anita; Lidya Rahmi; Zulhermindra Zulhermindra (PAEDAGOGIA, 2025)
Students in writing class frequently encounter obstacles in grasping learning materials due to the unattractive learning media used by the lecturers. Lecturers also struggle to identify instructional media that can cover the dense learning materials to stimulate students’ engagement and enhance learning outcomes. The e-book was developed to address these issues by integrating Islamic values and multimodal elements. This study aims to develop integrated Islamic values e-books as learning media in writing classes, particularly in genre-based writing subjects, through design and development research (DDR). There were three types of questionnaires distributed to the respondents throughout the study: need analysis (54 English Education department students), design and development (4 expert panels), and evaluation (23 English Education students). Descriptive and thematic analysis were employed to analyze data. The need analysis shows that students need learning media that can overcome problems in comprehending learning materials related to the process of writing essays and essay structures and in having sufficient time to learn genre-based writing subjects. During the design and development phase, it was found that the integrated Islamic values e-book is very feasible for both content and media aspects, with average scores of 4,25 (85%) and 4,61 (92,10%). After the results were validated, the integrated e-book was revised as suggested by both content and media experts. For the evaluation phase, it displays that the integrated e-book is very feasible to be utilized as learning media in genre-based writing subjects with an average score of 4,03 (80,66%).